KEEFEKTIFAN MODEL PEMBELAJARAN CONCEPT SENTENCE TERHADAP KEMAMPUAN MENULIS PARAGRAF KELAS III SD NEGERI KARANGREJO 01 BONANG DEMAK - Anis Iqomatul Khaq, Muhajir (Universitas PGRI Yogyakarta, 2019)
AbstrakTujuan dalam penelitian ini adalah untuk mengetahui keefektifan model concept sentence terhadap kemampuan menulis paragraf siswa kelas III SD Negeri Karangrejo 01 Bonang Demak. Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar siswa pada kemampuan menulis paragraf kelas III di SD Negeri Karangrejo 01 Bonang Demak. Jenis penelitian ini adalah penelitian kuantitatif dalam bentuk Pre Experimental Design dengan bentuk One Group Pretest-Posttest Design. Data dalam penelitian ini diperoleh melalui observasi dan dokumentasi. Hasil penelitian ini menunjukkan bahwaÂ modelÂ concept sentence terbukti efektif terhadap kemampuan menulis paragraf siswa kelas III SD Negeri Karangrejo 01 Bonang Demak dengan diperoleh hasil prosentase siswa tuntas 70% dan prosentase tidak tuntas 30%. Uji t yang diperoleh ð‘¡â„Žð‘–ð‘¡ð‘¢ð‘›ð‘” > ð‘¡ð‘¡ð‘Žð‘ð‘’ð‘™ yaitu 6,571287 > 2,093maka Ha diterima. Sehingga dapat disimpulkan model concept sentence efektif terhadap kemampuan menulis paragraf siswa kelas III semester 2 SD Negeri Karangrejo 01 Bonang Demak.Kata kunci : menulis paragraf, concept sentence, hasil belajarÂ AbstractThe purpose of this study was to determine the effectiveness of the concept concept model on the ability to write paragraphs of Grade III students of Karangrejo State Elementary School 01 Bonang Demak. This research is motivated by the low student learning outcomes in the ability to write class III paragraphs in Karangrejo Elementary School 01 Bonang Demak.Â This type of research is quantitative research in the form of Pre Experimental Design in the form of One Group Pretest-Posttest Design. The data in this study were obtained through observation and documentation. The results of this study indicate that the model concept sentence proved effective against the ability to write paragraphs of third grade students of Karangrejo State Elementary School 01 Bonang Demak with the results of the percentage of students completed 70% and the percentage not complete 30%. The t test obtained by t_count> t_table is 6.571287> 2.093, then Ha is accepted. So that it can be concluded that the model concept sentence is effective against the ability to write paragraphs of third grade students in the second semester of SD Negeri Karangrejo 01 Bonang Demak.Keywords: writing paragraphs, concept sentences, learning outcomes